87 Defining endothelial CD47 signalling in heart failure. (17th July 2020) - Haines, Zoe; Whitley, Guy; Clerk, Angela; Meijles, Daniel
Abstract : Introduction: Cardiac endothelial cell (EC) dysfunction and death is emerging as a key cause of heart failure, particularly in which ejection fraction is preserved (HFpEF). Of most concern, 50% of new heart failure patients are defined as HFpEF, and this is now the largest unmet cardiovascular complication in the field. ECs express the CD47 receptor which is ascribed an anti-angiogenic signalling role via control of nitric oxide signalling. However, more recent evidence suggests that activation of CD47 by its cognate ligand thrombospondin-1 (TSP1) can promote cellular oxidative stress caused by upregulation and activity of the reactive oxygen species (ROS) producing NADPH oxidase NOX1, which leads to cellular senescence. How CD47 regulates NOX1 in ECs and the overall role of CD47 in the progression to heart failure is poorly understood. Therefore, in this work we explored the effects of CD47 activation on intracellular ROS stress signalling pathways. Methods: . An archive of consented human left ventricular tissue from control (n=12) and non-ischemic heart failure (n=12) individuals was used in this study. To assess EC CD47 signalling the SGHEC-7 cell line was used and stimulated with 7N3 (10 μM), a peptide region of the cognate CD47 ligand thrombospondin-1. To contrast the effects of 7N3 on cells, the pro-stress and hypertension hormone angiotensin-II (AngII, 100 nM) was used. Left ventricular tissue and EC ROS generation was assessed by the cytochrome c reduction (superoxide) and Amplex Red (hydrogen peroxide) assays respectively. The expression of CD47-NOX1 pathway players and effect of EC-CD47 activation on mitogen-activated protein kinase pathways (MAPKs) was assessed by western blot analysis. Results: . Human non-ischaemic heart failure is associated with significantly elevated protein abundance of TSP1 (6.5 fold; p<0.01, t-test) and NOX1 (8.6-fold; p<0.05, t-test). Moreover, heart failure was linked to elevated hydrogen peroxide levels (1.1-fold; p<0.05, t-test) but not superoxide production. In ECs, acute time-course stimulation with 7N3 caused increased activation of the ERK1/2 and p38-MAPK (both maximal at 5 min), but with limited effect on EC-JNKs. These findings were similar with AngII stimulation, where ERK1/2 and p38-MAPK activation were maximal also at 5 min, but AngII activated JNKs with the maximum between 30-60 min. At the RNA level, it was found that 7N3 promoted increased NOX1 expression at 2 h and this was mirrored at the protein level. Conclusion: Here, we provide evidence that TSP1-CD47-NOX1 may play a role in the setting of human heart failure. Moreover, we demonstrate that EC CD47 stimulates stress-responsive MAPK pathway activation. Therefore, EC-CD47 may represent a novel target in the context of heart failure. Conflict of Interest: No